Inovasi Pelayanan Publik melalui Aplikasi “Pantai Balikpapan” oleh Dinas Kependudukan Dan Pencatatan Sipil Kota Balikpapan - Jihan Fadhila; Muhammad Jamal (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This research aims to understand and describe the online-based innovation of Pantai Balikpapan conducted by the Department of Population and Civil Registration of Balikpapan City. It also aims to identify the inhibiting and supporting factors in the implementation of the Pantai Balikpapan innovation at the Department of Population and Civil Registration of Balikpapan City. The research results indicate that the Public Service Innovation through the